Guidelines for reporting health research : a user's manual - Moher, David, 1957-; Altman, Douglas G.; Schulz, Kenneth F.; Simera, Iveta; Wager, Elizabeth; Wiley InterScience (Online service) (Chichester, West Sussex ; Hoboken, NJ : Wiley, 2014)
Guidelines for Reporting Health Research is a practical guide to choosing and correctly applying the appropriate guidelines when reporting health research to ensure clear, transparent, and useful reports. This new title begins with an introduction to reporting guidelines and an overview of the importance of transparent reporting, the characteristics of good guidelines, and how to use reporting guidelines effectively in reporting health research. This hands-on manual also describes over a dozen internationally recognised published guidelines such as CONSORT, STROBE, PRISMA.
Current version compared with the previous versionsExtensions and/or implementations; How best to use the guideline; Evidence of effectiveness of guideline; Endorsement and adherence; Cautions and limitations (including scope); Mistakes and/or misconceptions; Creators' preferred bits; State how participants were allocated to interventions; For the primary outcome, a result for each group and the estimated effect size and its precision should be stated; Include the registration number and name of trial register; Future plans; Acknowledgments; References; Chapter 9 CONSORT; Name of guideline.
When to use CONSORT.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on October 21, 2014).
Keywords: Medicine -- Research -- Authorship; Medicine -- Research -- Evaluation; Report writing; Biomedical Research -- methods; Research Report -- standards; Peer Review, Research -- standards; Electronic books